Identity in Persian Egypt: the fate of the Yehudite community of Elephantine - Becking, Bob (Eisenbrauns, 2020)
Intro -- COVER Front -- Copyright Page -- Table of Contents -- Introduction -- Chapter 1: How Persian Power Entered Egypt -- Chapter 2: Yehudites at Elephantine: Provenance, Identity,and Religion -- Chapter 3: Multiethnic Elephantine: Some Remarkson Different Minor Ethnicities in a Persian Border Garrison -- Chapter 4: Pax Persica: Cooperation, Cohabitation, and Acceptance -- Chapter 5: Control Through Education, Law, and Military Power -- Chapter 6: Disruptions of the Interethnic Solidarity -- Chapter 7: "Khnum Is Against Us Since Hananiah Has Been in Egypt": On Two Historical Movements in the Fifth Century BCE -- Chapter 8: Beyond the Final Curtain:The Aftermath of Elephantine -- BiBLIOGRAPHY -- Index.